Pengenalan Pengelolaan Lingkungan melalui Kegiatan Sains Dasar Sederhana Berdampak dan Berkelanjutan - Rita Rahmaniati; Bulkani; Sari Marlina; Amelia Dwi Astuti; Muh. Azhari (Kreasi: Jurnal Inovasi dan Pengabdian kepada Masyarakat, 2026)
The continuously changing state of the environment—in terms of both quality and quantity—necessitates consistent measures to preserve and protect existing conditions and ensure the sustainability of life components such as humans, animals, and plants. Supporting environmental components—such as water, soil, air, and light—must be preserved. The quality of these components influences the condition of other elements of life. The activities aim to accustom children to being responsive to environmental conditions and to enable them to serve as a local environmental mitigation group. The method employed in this community service activity involves a practical, simple science approach—specifically, observing unfavorable environmental conditions and providing solutions to the problems encountered. This community service activity involved upper-grade elementary students from SDN 07 Panarung, Palangka Raya. The results demonstrated the students' enthusiasm for the material—which covered simple environmental management and basic science practices, such as simple water filtration—addressing the issue of water quality in Palangka Raya, This is evident from the activities repeatedly undertaken by highly curious participants, ensuring that the measures taken yield benefits for environmental management in both the short and long term (sustainability).